2022
DOI: 10.1088/1361-6463/ac5da3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on performance of ultra-thin GaAs solar cells enabled with frontal surface pyramid array

Abstract: In this paper, the optical and electrical characteristics of ultra-thin GaAs solar cell with front-surface pyramid array are investigated systematically. The results show that the cell with pyramid array could significantly improve the photon absorption efficiency due to synergistic effects of antireflection and diffraction compared with reference solar cells with single and double anti-reflective coating (ARC), and the maximal integrated quantum efficiency of 0.88 is obtained for pyramid cells, much higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[99] According to Peng et al, modified chitosan-based nanosilver has a notable inhibitory impact on typical bacterial infection and diminishes the incidence of umbilical cord wound inflammation. [100] Shehabeldine et al investigated the antimicrobial and antiviral properties of long-lasting cotton garments treated with nanoparticles of zinc oxide, acyclovir, clove oil, and nano chitosan. The results showed that the treated cotton garments had more promising antibacterial action towards Gram-positive bacteria than Gram-negative bacteria.…”
Section: Chitosan/nanoparticles-based Cotton Fabric Compositesmentioning
confidence: 99%
“…[99] According to Peng et al, modified chitosan-based nanosilver has a notable inhibitory impact on typical bacterial infection and diminishes the incidence of umbilical cord wound inflammation. [100] Shehabeldine et al investigated the antimicrobial and antiviral properties of long-lasting cotton garments treated with nanoparticles of zinc oxide, acyclovir, clove oil, and nano chitosan. The results showed that the treated cotton garments had more promising antibacterial action towards Gram-positive bacteria than Gram-negative bacteria.…”
Section: Chitosan/nanoparticles-based Cotton Fabric Compositesmentioning
confidence: 99%
“…In order to reduce the cost and optical losses, various strategies to reduce the reflection and enhance the absorptance by utilizing random or periodically arranged nanopatterns or plasmonic nanoparticles are implemented [11,12]. In addition to this, different nanostructures such as nanocones [13,14], nanoholes [15][16][17], nanowire [13,14], nanopyramids [18][19][20], funnel [13], inverted nanopencil [21] etc used in the active layer of SCs can improve the light trapping and carrier collection efficiency to a large extent in comparison to the thin film planar SCs. Arrays of different nanostructures act as perfect light absorbers due to their ability to optimize the optical path length of incident photons and reduce their escape probability from the surface and relax the stringent criterion of lattice matching for the growth of different materials on flexible and low-cost substrates [13].…”
Section: Introductionmentioning
confidence: 99%
“…GaAs is widely used for photovoltaic and photothermal applications due to its superior optoelectronic properties such as direct bandgap, high mobility, high absorption coefficient and ideal solar spectral response [22,23]. However, the high manufacturing cost of GaAs materials restricts its usage in terrestrial applications and necessitates the thinning of the active layer to reduce material cost, purity and crystallinity requirements [20,24]. Thin film GaAs SCs suffer from low photoconversion efficiency due to limited absorption by the thin active layer.…”
Section: Introductionmentioning
confidence: 99%